Clinical significances of prothrombin time-international normalized ratio and activated partial thromboplastin time in patients with atrial fibrillation treated with direct oral anticoagulants. (14th October 2021) - Chao, T; Chan, Y.H; Chen, S.A
Abstract: Background: Although the measurements of PT-INR or aPTT were not performed for patients with atrial fibrillation (AF) taking direct oral anticoagulants (DOACs) in randomized trials, these tests were commonly used and familiar to clinical physicians. We aimed to test whether there is an association between PT-INR or aPTT ratio and risks of ischemic stroke/systemic embolism (IS/SE) and major bleeding among AF patients taking rivaroxaban or dabigatran, respectively. Methods: This multi-center cohort study included 3, 192 AF patients taking rivaroxaban and 958 patients taking dabigatran for stroke prevention whose data about PT-INR and aPTT were available. Results: For patients treated with rivaroxaban, a higher INR level was not associated with a higher risk of major bleeding compared to an INR level <1.1. The risk of IS/SE was lower for patients having an INR ≥1.5 compared to those with an INR <1.1 (aHR: 0.57; [95% CI: 0.37–0.87]; P=0.0088) (Figure). On-label dosing of rivaroxaban and use of digoxin were independent factors associated with an INR ≥1.5 after taking rivaroxaban. For patients taking dabigatran, a higher aPTT ratio was not associated with a higher risk of major bleeding. The risk of IS/SE was lower for patients having an aPTT ratio of 1.1–1.2 and 1.3–1.4 than those with an aPTT ratio <1.1. Conclusions: In Asian AF patients, PT-INR or aPTT ratios were not associated with the occurrences of bleeding events for rivaroxaban or dabigatran. Patients taking rivaroxaban with an INR ≥1.5 were associated with a lower risk of IS/SE. Appropriate dosages of DOACs and the compliances of patients should be confirmed for patients taking rivaroxaban with an INR <1.5. Funding Acknowledgement: Type of funding sources: None.